Selenium health impacts and Sub-Saharan regional nutritional challenges: Review - Loti Kasezga Botha; Sydney Namaumbo; Noel Jabesi Kapito; Patrick Ndovie; Deborah Charles Tsukuluza; Fatema Jagot; Angstone Thembachako Mlangeni (Results in Chemistry)
Selenium is an important micronutrient that plays key functions in antioxidant defense, immune function, and thyroid health. However, its benefits and risks are closely linked to selenium methylation, a process that significantly influences its biological activity and potential toxicity. This review critically analyse the role of selenium methylation in modulating selenium’s effects on health, highlighting its impact on both protective and adverse outcomes. it also discusses the current understanding of selenium’s essential functions and toxicity risks, emphasizing the complexities of Se methylation. The review addresses notable research gaps and controversies, including inconsistent findings on selenium’s cancer-preventive properties, the diverse biological activities of different selenium species, and the challenges in determining optimal selenium intake levels. By synthesizing existing knowledge and identifying key areas for further investigation, this review aims to advance readers’ understanding of selenium’s multifaceted roles that guide future research and public health strategies.